An Outdoor Access Period Improves Chicken Cecal Microbiota and Potentially Increases Micronutrient Biosynthesis - Varriale, Lorena; Coretti, Lorena; Dipineto, Ludovico; Green, Brian D.; Pace, Antonino; Lembo, Francesca; Menna, Lucia Francesca; Fioretti, Alessandro; Borrelli, Luca (Frontiers in Veterinary Science, 2022)
Characterizing the gut microbiota of free-range and alternative poultry production systems provides information, which can be used to improve poultry welfare, performance, and environmental sustainability. Gut microbiota influence not only the health and metabolism of the host but also the presence of zoonotic agents contaminating food of animal origin. In this study, the composition and diversity of the cecal microbiota community of free-range grown chickens were characterized by 16S rDNA high-throughput Illumina sequencing. Significant differences were observed in the composition of chicken cecal microbiota at the time points of 28 days of age (Indoor group) and 56 days of age (Outdoor group), i.e., before and after the outdoor access period of chicken groups. The Outdoor group showed a richer and more complex microbial community, characterized by the onset of new phyla such as Deferribacterota and Synergistota, while the Indoor group showed an increase in Campylobacterota. At the species level, it is noteworthy that the occurrence of Mucispirillum schaedleri in Outdoor group is known to potentially stimulate mucus layer formation in the distal intestinal tract, thus being associated with a healthy gut. We also report a significant decrease in the Outdoor group of Helicobacter pullorum, highlighting that the lower abundance at the age of slaughter reduced the possibility to contaminate chickens' carcasses and, consequently, its zoonotic potential. As revealed by a mutual exclusion study in network analysis, H. pullorum was present only if Bacteroides barnesiae, an uncultured organism of the genus Synergistes, and Bacteroides gallinaceum were absent. Finally, microbiome predictive analysis revealed an increase of vitamins and micronutrient biosyntheses such as queuosine (Q) and its precursor pre Q0, in the Outdoor group, suggesting that the outdoor evolved microbiota of chickens do contribute to the vitamin pool of the gut and the biosynthesis of micronutrients involved in vital cell processes.